Pengaruh struktur aktiva, profitabilitas, pertumbuhan penjualan, kebijakan deviden dan resiko bisnis terhadap struktur modal pada perusahaan Food And Beverages yang terdaftar di BEI periode 2010-2012 - Christina Wijaya; Restu Agusti; Yesi Mutia Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This reserach aims to examine and analyze how the effect of asset structure, profitability, sales growth, dividend policy and business risk on capital structure at Food And Beverages companies listed in Indonesia Stock Exchange for 3 years 2010-2012.The analytical method used is multiple regression. Before the t test, first test the classical assumption of normality of the data, autocorrelation, multicollinearity and heteroscedasticity. Once free of the classical assumptions, hypothesis testing using t-test to see the effect of each independent variable on the dependent variable partially.The results of this analysis it is known that the structure of assets and sales growth affects the capital structure. While profitability, dividend policy and business risk does not affect the capital structure of the company 2010-2012 Food And Beverages.Keywords : Capital structure, asset structure, profitability, sales growth, dividend policy and business risk.